2018
DOI: 10.1186/s40425-018-0413-z
|View full text |Cite
|
Sign up to set email alerts
|

Response to PD1 inhibition in conventional chondrosarcoma

Abstract: BackgroundChondrosarcoma is one of the most common malignant bone tumors in adults. Conventional chondrosarcoma represents around 85% of all chondrosarcomas and is notoriously difficult to treat with chemotherapy.Case presentationWe describe a 67-year-old man with metastatic conventional chondrosarcoma who was treated with nivolumab. Treatment was discontinued after restaging showed increased tumor burden, which later proved to be pseudoprogression. The patient restarted nivolumab and continues to have a near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Nivolumab is another PD-1 blocker, which has been the primary focus of several case reports and phase II clinical studies for the treatment of soft tissue sarcoma. It was previously hypothesized that nivolumab may serve a definite role in the treatment of soft tissue sarcoma (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab is another PD-1 blocker, which has been the primary focus of several case reports and phase II clinical studies for the treatment of soft tissue sarcoma. It was previously hypothesized that nivolumab may serve a definite role in the treatment of soft tissue sarcoma (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 2 study evaluating the anti-PD1 antibody nivolumab, one patient with dedifferentiated chondrosarcoma showed partial response [57]. In another report, one patient with metastatic conventional chondrosarcoma treated with nivolumab had a favorable response [58]. There are several trials currently underway evaluating anti-PD1 antibodies in sarcomas including chondrosarcomas.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Two of four patients with alveolar soft part sarcoma were reported to have partial response to anti-PD-L1 therapy [18]. A microsatellite instability (MSI), low tumor mutation burden (TMB) chondrosarcoma with 1% PD-L1 positivity, was reported to respond to nivolumab [19]. Finally, the SARC028 clinical trial reported that 18% of patients with mesenchymal tumors had an objective response to pembrolizumab.…”
Section: To the Editormentioning
confidence: 99%